Computation for humanity : information technology to advance society - Zander, Justyna; Mosterman, Pieter J. (2014)
"This book discusses various aspects computational science and engineering in combination with applied science. It also highlights sustainability to demonstrate how computation can improve different aspects of life. The editors provide a collection of numerous computation-related projects that form a foundation to cross-pollinate between different disciplines and further extensive collaboration. They also present a clear and profound understanding of computing in today's world. The detailed application examples provide the reader \vith contributions that behold approaches to provide fundamental solutions to some of the most pertinent humanity-related problems"--
"Through the ages, indeed millennia, humans have been exceptionally ingenious and adept at exploiting nature to develop tools for their benefit. Better understanding nature is thus nothing short of a guarantee for the development of novel tools. Never before had this been put on display as prominently as with the formulation of a fundamental scientific approach to the study of nature (Chapter 13). The systematic development of knowledge that derives from such study provided a rapidly expanding body of intelligence to the avail of technological exploitation. And it should come as no surprise that humanity indeed capitalized on the technological opportunities like never before in history (e.g., steam engine, reciprocating engine, pendulum clock, navigation, etc.)"--
Keywords: Social sciences -- Data processing; COMPUTERS / Software Development & Engineering / Systems Analysis & Design; MATHEMATICS / General; TECHNOLOGY & ENGINEERING / Electronics / General